Ecological parasitology reflections on 50 years of research in aquatic ecosystems - Esch, Gerald W.; Allen, Charles M. (John Wiley & Sons, 2016)
Professor Gerald Esch has already published two books in what is becoming an informal series of essays exploring the way that discoveries about the biology of parasites have influenced ecological and evolutionary theories over a career that has spanned nearly 50 years. This book will be the third set of essays and will focus on key moments of discovery and explore how these achievements were due to collaboration, mentoring, and community building within the field of ecological parasitology. The book will not only describe case studies, pure science and biology but also act as a career guide for early-career ecologists emphasizing the importance of collaboration in the advancement of science.--Provided by publisher.